Dopamine-modified aramid fibers reinforced epoxidized natural rubber nanocomposites. (January 2022) - Gong, Xianyun; Liu, Yuyan; Huang, Mina; Dong, Qingliang; Naik, Nithesh; Guo, Zhanhu
Abstract: Via the amino activity of dopamine, poly(dopamine) (PDA) is covered on the surface of aramid fibers (AFs) by a simple dip coating method. Benzoyl aniline is used as a model compound of AF to disclose the action between dopamine and AF. PDA does not produce a chemical bond between coating and AFs. The self-polymerized PDA coating and following epoxidized natural rubber (ENR) grafting on the AF surface contribute to the improved surface roughness and surface activity. The interface strength is increased by 37% with the concentration of dopamine at 2 g/L and ENR at 40 g/L. Graphical abstract: Image 1 Highlights: The self-polymerized polydopamine) (PDA) layer was deposited on aramid fibers (AFs). AFs were functionalize based on dopamine chemistry, i.e., hydrophilic and oleophilic functionalization. Using polydopamine as a bridge, the functionalized AFs were prepared into rubber composites after following ENR grafting. PDA coating and further ENR grafting significantly improved the mechanical properties.